2019
DOI: 10.13005/bpj/1813
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Losartan on Different Biochemical Parameters in Essential Hypertensive Patients

Abstract: The renin–angiotensin system (RAS) provides the most powerful regulation of blood pressure and angiotensin II is the primary mediator in this system. The binding of angiotensin II to AT1 receptors produces a number of potentially harmful effects that include increase in blood pressure, progression of atherosclerosis, myocardial and vascular hypertrophy. Losartan was the first ARB and found to reduce the risk of stroke, new onset of diabetes and to have a proven benefit in stroke. The present study was designed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
1
0
0
Order By: Relevance
“…Looking at the trend of the urinary Na + excretion values of losartan-treated rats at week 4 (Table 2), it is possible that we might see some significant changes if the treatment is continued for more than 4 weeks. The findings in the current study are, nevertheless in line with recent findings by Salve et al (2019) who showed no changes in the serum concentration of sodium, potassium and calcium after 6 months of losartan therapy in patients with essential hypertension [24].…”
Section: Discussionsupporting
confidence: 93%
“…Looking at the trend of the urinary Na + excretion values of losartan-treated rats at week 4 (Table 2), it is possible that we might see some significant changes if the treatment is continued for more than 4 weeks. The findings in the current study are, nevertheless in line with recent findings by Salve et al (2019) who showed no changes in the serum concentration of sodium, potassium and calcium after 6 months of losartan therapy in patients with essential hypertension [24].…”
Section: Discussionsupporting
confidence: 93%